2011
DOI: 10.2215/cjn.10241110
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Thiosulfate Pharmacokinetics in Hemodialysis Patients and Healthy Volunteers

Abstract: SummaryBackground and objectives Vascular calcification is a major cause of morbidity and mortality in dialysis patients. Human and animal studies indicate that sodium thiosulfate (STS) may prevent the progression of vascular calcifications. The pharmacokinetics of STS in hemodialysis patients has not been investigated yet.Design, setting, participants, & measurements STS was given intravenously to 10 hemodialysis patients onand off-hemodialysis. Additionally, STS was applied to 9 healthy volunteers once intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
1
50
0
2
Order By: Relevance
“…clinical settings to treat caliciphylaxis, extravasations during chemotherapy or cyanide poisoning (50), and is also a component of the transsulfuration pathway. Used as a substrate for rhodanaselike enzymes, thiosulfate could also be a source of targeted persulfidation, as recently proposed by Mishanina et al (31).…”
Section: Treatment With Sodium Thiosulfate Reduces Eye Degeneration Imentioning
confidence: 99%
“…clinical settings to treat caliciphylaxis, extravasations during chemotherapy or cyanide poisoning (50), and is also a component of the transsulfuration pathway. Used as a substrate for rhodanaselike enzymes, thiosulfate could also be a source of targeted persulfidation, as recently proposed by Mishanina et al (31).…”
Section: Treatment With Sodium Thiosulfate Reduces Eye Degeneration Imentioning
confidence: 99%
“…Cicone et al first reported that administration of sodium thiosulfate (STS) may be useful in treating CUA (15). Although the exact mechanism of action is unknown (16,17), several case reports and small case series have been published on STS administration for CUA (17). However, published data on STS have been mixed, with some demonstrating beneficial effects (18)(19)(20) and others showing no benefit (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous and intraperitoneal administration of STS in hemodialysis and peritoneal dialysis patients are well tolerated and adverse events are mild [66][67][68] . STS is readily cleared by dialysis [69] . In two preliminary studies in hemodialysis patients, STS was able to delay the progression of CAC after 4-5 mo of twice weekly intravenous administration but with a decline of hip bone mineral density in one study [67,70] .…”
Section: Sodium Thiosulfatementioning
confidence: 99%